Revolusi Industri 4.0: Inovasi dan Tantangan dalam Pendidikan di Indonesia - Fitrianti, Eka; Annur, Saipul; Afriantoni (Journal of Education and Culture, 2024)
The Industrial Revolution 4.0 brings significant innovations and challenges to the education sector in Indonesia. As one of the main pillars for the advancement of future generations, the education sector faces major challenges in adapting to rapid technological developments. The era of the 4.0 revolution demands that the education sector adapt to continuously evolving technology and leverage the ease of access to information and communication technology to support the learning process. Technological disruption, which is a hallmark of the industrial revolution 4.0, has a major impact on changes in the current educational landscape. The methods used in this article include literature analysis and case studies at several educational institutions in Indonesia that have implemented 4.0 technology in the learning process. The discussion in this article covers the identification of technological innovations that have been integrated into the curriculum, changes in teaching methods, and the development of digital competencies among students and educators. The results of the study indicate that the integration of technology in education increases the effectiveness of learning, although there are challenges in its implementation, such as infrastructure limitations and the readiness of human resources. This transformation is expected to create a generation ready to face future challenges and contribute to the nation's progress. The article concludes that despite the challenges that must be overcome, the benefits of applying technology in education are far greater and essential to creating a learning environment relevant to the needs of the 21st century.